Radiofrequency Ablation of Benign Thyroid Nodules and Recurrent Thyroid Cancers: Consensus Statement and Recommendations - Lee, Jeong Hyun; Jung, So Lyung; Kim, Ji-hoon; Sung, Jin Yong; Shin, Jung Hee; Kim, Eun-Kyung; Lee, Joon Hyung; Kim, Dong Wook; Park, Jeong Seon; Kim, Kyu Sun; Baek, Seon Mi; Lee, Younghen; et al. (Korean journal of radiology, 2012)
Thermal ablation using radiofrequency is a new, minimally invasive modality employed as an alternative to surgery in patients with benign thyroid nodules and recurrent thyroid cancers. The Task Force Committee of the Korean Society of Thyroid Radiology has developed recommendations for the optimal use of radiofrequency ablation for thyroid nodules. These recommendations are based on a comprehensive analysis of the current literature, the results of multicenter studies, and expert consensus.